ANALISIS BENTUK DAN KOMPOSISI MUSIK SPEECH COMPOSING HOTTO DOGU KARYA HEIAKIM MUSIK DENGAN MEDIA GOOGLE TRANSLATE - Rico Kristian Saputra (Repertoar, 2020)
The development of music technology came within time to time with a variety of innovations and new discoveries in music. Development grow faster in the music industry, more and more appear in musical works. Followed by the development of music, the technology is also being used, so that digital music trends are emerging. One result of development of digital music technology is speech composing. In a simple speech that compiles interpreted as a process of creativity that turns words into songs. Heiakim Music, who made the Speech Composings  song "Hotto Dogu" whose lyrics were taken from pieces of words made from sound samples using Google Translate feature (Text to Speech).